Analysis of the Influence of Entrepreneurial Motivation, Product Innovation and Business Strategy on Business Performance : Survey: Dry Cake UMKM in Sukabumi City - Mulyana, Muhamad; Danial, R. Deni Muhammad; Zafar, Tetty Sufianty (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine the effect of entrepreneurial motivation, product innovation, and business strategy on business performance in pastry MSME players in Sukabumi City. This study uses a quantitative approach with a population of all pastry MSME players in Sukabumi City and saturated sampling techniques, so that the number of respondents is 33 pastry MSME business actors. Data collection techniques were carried out through distributing questionnaires with Likert scale measurements. Data analysis was conducted using research instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS version 26. The results showed that entrepreneurial motivation did not have a significant effect on business performance. Meanwhile, product innovation and business strategy have a positive and significant effect on business performance.